1984
DOI: 10.1007/bf02542155
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of cholesterol oxides in grated cheese and bleached butteroil

Abstract: Butteroil samples bleached with benzoyl peroxide (BP) and 17 commercial cheeses were screened for oxidized sterols by thin layer chromatography (TLC). Ungrated cheeses made from bleached milk and freshly bleached butteroil contained no detectable oxidized sterols. Oxidized sterols were detected in stored, bleached butteroils and in grated cheeses. Four major oxidation products were the isomeric 5,6‐epoxycholesterols and the epimeric 7‐hydroxycholesterols identified by TLC, high performance liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 26 publications
2
26
1
1
Order By: Relevance
“…In the opinion of Nourooz-Zadeh and Appleqvist (1988b), the analytical data of Fischer, Laskawy, and Grosch (1985) who saponified total lipids, include esterified sterol oxides as some artefacts were generated. The method (TLC analysis) used by Finocchiaro, Lee, and Richardson (1984) also appears to yield values which are higher than results using other methods.…”
Section: Methods For Determination Of Cops In Milk and Dairy Productsmentioning
confidence: 53%
See 2 more Smart Citations
“…In the opinion of Nourooz-Zadeh and Appleqvist (1988b), the analytical data of Fischer, Laskawy, and Grosch (1985) who saponified total lipids, include esterified sterol oxides as some artefacts were generated. The method (TLC analysis) used by Finocchiaro, Lee, and Richardson (1984) also appears to yield values which are higher than results using other methods.…”
Section: Methods For Determination Of Cops In Milk and Dairy Productsmentioning
confidence: 53%
“…In the first 20 days, only a small amount of COPs was found in grated cheese under fluorescent light, the formation of 7-ketocholesterol was faster than 7a-and 7b-hydroxycholesterol whereas aand b-epoxide remained nearly constant for 72 days (Nielsen et al, 1995). According to Finocchiaro et al (1984), the levels of 5,6-epoxycholesterol, 7a-and 7b-hydroxycholesterol were higher in grated Parmesan cheese packaged in glass than the same grated cheese packaged in a cardboard box. Exposure of cheese powders to fluorescent light (1611 lux) for 12 weeks increased the levels of a-epoxide and 7-ketocholesterol, Table 7 COP levels (mg kg À1 fresh product) in stored butter after exposure to light at cooling and room temperature (Hiesberger & Luf, 2000) Butter with the levels being highest after 3 weeks and then decreasing throughout the remaining weeks to about half (Sander et al, 1989b).…”
Section: Cops In Dairy Products After Light Exposurementioning
confidence: 80%
See 1 more Smart Citation
“…Cholesterol oxides are usually found to accumulate at a relatively high level in commercially available fish products (1,2), and similarly in other processed foods such as spray-dried egg and milk products (3,4), heated oils and fats (5)(6)(7)(8)(9)(10) and processed meat products (11,12). We have studied the mechanism involved in cholesterol oxidation in fish products, and reported that there was a significant correlation between the peroxide values and the levels of cholesterol oxides in an oxidized mixture of cholesterol and purified fish oils.…”
Section: Introductionmentioning
confidence: 99%
“…Embora seja eficiente para separar alguns produtos da oxidação do colesterol, a CG pode também destruir termicamente o colesterol e os hidroperóxidos [6,31]. A cromatografia gasosa com espectrometria de massas (CG-MS) é também uma técnica particularmente eficaz para a confirmação dos óxidos de colesterol [16,20,24].…”
Section: Introductionunclassified